1988
DOI: 10.1007/bf02370108
|View full text |Cite
|
Sign up to set email alerts
|

Persistence and competitiveness of threeBradyrhizobium japonicum inoculant strains in clay loam Nile valley soil

Abstract: The survival and persistence of three B. japonicum inoculant strains USDA 110, USDA 138 and TAL 379 were studied in a clay loam Nile valley soil. The inoculated field plots in the summer of 1985 were sown with soybean again in 1986 season. No inoculation in the season of 1986 was conducted and the plants were left to nodulate with the persisted cells of the inocula strains applied a year before. The soil had no background of B.japonicum, however, some nodules were formed on the control plants due to the carryo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
3
0

Year Published

1990
1990
2005
2005

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
2
3
0
Order By: Relevance
“…The highest N accumulation in clay soil was found in the treatment previously inoculated with CE3, whereas in silty loam soil the largest N accumulation was found with strain Ph 163. These results are in agreement with those obtained by other investigators, who found that the soybean and lintel rhizobia were able to survive and persist in clay loam soil for three successive seasons after the first inoculation (MOAWAD et al 1988(MOAWAD et al , 1994.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The highest N accumulation in clay soil was found in the treatment previously inoculated with CE3, whereas in silty loam soil the largest N accumulation was found with strain Ph 163. These results are in agreement with those obtained by other investigators, who found that the soybean and lintel rhizobia were able to survive and persist in clay loam soil for three successive seasons after the first inoculation (MOAWAD et al 1988(MOAWAD et al , 1994.…”
Section: Discussionsupporting
confidence: 93%
“…The strains were able to survive and persist for the whole year in both soil types prevailing in the major bean production areas, and the competition for nodulation is a major limiting factor for the full utilization of the symbiotic advantages of the selected rhizobial strains. This is in agreement with the work conducted by other scientists in the field of Biological Nitrogen Fixation (MOAWAD et al 1988, YOU et al 1998, AGUI-LAR et al 2001, KAOUTHAR et al 2001, LOPEZ-GARCIA et al 2002, SONIA et al 2002. This also shows the need for deeper understanding of competition attributes to find a way to reduce the nodulation by unknown native rhizobia and enhance the formation of plantrhizobia symbiotic systems with promising strains of rhizobia.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The ability of a rhizobial strain to adapt to prevailing soil conditions and to persist into subsequent growing seasons is an important consideration in selecting inocula (Brunei et al, 1988;Moawad et al, 1988). Brockwell et al (1985) used antibioticresistant strains to inoculate a soil free of B. iaponicum.…”
Section: Establishment Of Rhizobial Inoculants In the Fieldmentioning
confidence: 99%